2011
DOI: 10.1055/s-0031-1277137
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hypothyroidism Associated with Acute Mania: Case Series and Literature Review

Abstract: In the evaluation of patients presenting with altered mental function searching for underlying medical conditions is necessary. Abnormal thyroid function has long been implicated in mood changes with the classic associations of depression occurring together with hypothyroidism and of mania along with hyperthyroidism. We here report 3 patients who presented with symptoms consistent with acute manic episode diagnosed using DSM IV-TR criteria and who were found to have primary hypothyroidism biochemically. This l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
0
25
0
2
Order By: Relevance
“…The potential mechanisms of action include the interaction of thyroid hormones and neurotransmitters. It has been shown that an enhanced activity of the enzyme tyrosine hydroxylase is related to increased concentrations of dopamine (DA) in the brain of hypothyroid rats, thereby leading to the manifestation of mania due to monoamine excess (10)(11)(12). Another hypothesis is based on serotonin activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential mechanisms of action include the interaction of thyroid hormones and neurotransmitters. It has been shown that an enhanced activity of the enzyme tyrosine hydroxylase is related to increased concentrations of dopamine (DA) in the brain of hypothyroid rats, thereby leading to the manifestation of mania due to monoamine excess (10)(11)(12). Another hypothesis is based on serotonin activity.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is based on serotonin activity. It has been reported that in the limbic system of the rat, hypothyroidism can cause a decrease in serotonin with the consequent up-regulation of dopamine postsynaptic receptors and increased dopamine activity in the brain, resulting in maniac symptoms (12,13). Furthermore, thyroid hormones have a modulating impact on the brain catecholamine system, regulating β-adrenergic receptor sensitivity, so that changes in hormone levels, as seen in hypothyroidism, might increase catecholamine action with major risk of mania in vulnerable individuals (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, cases with manic episodes related to primary hypothyroidism have been reported rarely (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…2 Clinical and subclinical hypothyroidism are sometimes observed in psychiatric disorders. For example, these endocrine states may be associated with developmental delay or mental retardation, 3 mood or cognitive disturbance in the elderly, 4 dementia, 5 psychosis, 6 depression, 7 bipolar disorder, 8 rapid-cycling mood disorder, 9 and other conditions. Hypothyroidism may also be an adverse outcome of lithium therapy.…”
mentioning
confidence: 99%